Kierunki badawcze dotyczące współpracy transgranicznej w administracji publicznej - Kusiak-Winter, Renata (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2015)
Research on cross-border cooperation must be placed in a larger context of research of Europeanization and internationalization of contemporary public administration. Administrative sciences have to analyze and critically asses instruments designed specifically to perform public tasks typical for border regions, but they should also point to all the mechanisms helpful in opening national administrations for interaction in the international environment.
Keywords: administrative sciences; internationalization of administration; Europeanization of administration; administrative law; border regions; cross-border cooperation